(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate, through a review of clinical trials, the importance of dental care and oral health care for patients in Intensive Care Units (ICUs), for the control of oral biofilm and respiratory infections. A search was carried out in the MEDLINE / PubMed and LILACS databases, using the descriptors “Dental Care”, “Hospital Dental Staff”, “Intensive Care Unit”, “Dentist, including only randomized clinical trials, published until July 2020, without restriction of language and country of study. The selected studies were submitted to initial screening based on the reading of titles, abstracts and full article, with duplicate studies being excluded. 43 articles were found, of which, only 10 randomized clinical trials were included in the present review. Considering the results found in the present review, the oral health of patients in ICUs, when neglected, can represent an important source of dissemination of respiratory infections, which highlights the importance of dental care and oral care in a hospital environment , with the use of 0.12% chlorhexidine, not associated with tooth brushing, to control oral biofilm and reduce the incidence of respiratory infections.